Staurastrum cyclacanthum var. pseudobrevissimus – a new variety of desmids and some other rare taxa found in peat bogs (Western Pomerania, Poland) - Komarzewska, Katarzyna; Kowalski, Wojciech W. A. (Annales Universitatis Paedagogicae Cracoviensis Studia Naturae, 2024)
New variety of Staurastrum cyclacanthum var. pseudobrevissimum and four other taxa: Korshikoviella limnetica, Polyedriopsis spinulosa, Monactinus simplex var. echinulatum and Cosmarium sp. rarely reported from the studied region of north-western Poland are noticed. For all of them, detailed descriptions with original documentation and ecological characteristics of the studied sites are presented in this article.